Coffee micro small medium enterprises development strategy in Sungai Penuh City, Jambi - Afdhal Chatra (Jurnal Mantik, 2023)
Sungai Penuh City is one of the cities in Jambi Province with great potential in developing micro, small, and medium enterprises (MSMEs); coffee and coffee is one of the leading commodities of Sungai Penuh City. The coffee industry in Sungai Penuh City has contributed to the local economy. However, the development of coffee MSMEs in the area is still not optimal. For this reason, a strategy is needed to develop coffee MSMEs in Sungai Penuh City by first conducting IFE and EFA analysis to determine the existing conditions of coffee MSMEs in Sungai Penuh City after knowing the internal and external factors; a SWOT analysis is carried out. The results of this study show that coffee MSMEs are on the criteria of maintaining and maintaining. Strategies that can be used in this hold and maintain position are market penetration strategies, market development, and product development